2008
DOI: 10.1093/aob/mcn107
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of Stomatal Traits and Carbon Isotope Discrimination in Two Hybrid Poplar Families (Populus deltoides ‘S9-2’ × P. nigra ‘Ghoy’ and P. deltoides ‘S9-2’ × P. trichocarpa ‘V24’)

Abstract: Genetic variation in stomatal traits and Delta was large within as well as between the different poplar species and their hybrids, but there were no direct relationships between stomatal traits and plant growth or Delta. As already noticed in various poplar hybrids, the absence of, or the weak, relationship between Delta and plant growth allows the possibility of selecting poplar genotypes combining high productivity and high WUE. In this study, stomatal traits are of limited value as criteria for selection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 56 publications
(95 reference statements)
5
61
0
Order By: Relevance
“…Few publications have analysed the relationship between Δ 13 C and stomatal density among genotypes. A positive relationship between Δ 13 C and stomatal density was also found for Pinus ponderosa provenances (Cregg et al, 2000) and among poplar clones from Populus deltoides × nigra hybrids (Monclus et al, 2006), whereas Dillen et al (2008) found a negative relationship for a Populus deltoides × trichocarpa family. Genotypes with larger stomatal density showed higher g s , which could lead to lower W i .…”
Section: Variables Driving Variation Of W I Within This Pedunculate Omentioning
confidence: 63%
“…Few publications have analysed the relationship between Δ 13 C and stomatal density among genotypes. A positive relationship between Δ 13 C and stomatal density was also found for Pinus ponderosa provenances (Cregg et al, 2000) and among poplar clones from Populus deltoides × nigra hybrids (Monclus et al, 2006), whereas Dillen et al (2008) found a negative relationship for a Populus deltoides × trichocarpa family. Genotypes with larger stomatal density showed higher g s , which could lead to lower W i .…”
Section: Variables Driving Variation Of W I Within This Pedunculate Omentioning
confidence: 63%
“…The low values of g s in Bakan agreed with the low values of g s observed at the same site, but in the second year of the plantation (2011; single stem) for Bakan and Skado ( P. trichocarpa  ×  P. maximowiczii ; Broeckx, Fichot, Verlinden, & Ceulemans, 2014). Leaves of P. deltoides (female parent of Oudenberg, Grimminge and Koster, but also 50% of the male parentage of Grimminge) have more stomata per leaf surface than leaves of P. trichocarpa (female parentage of Bakan; Al Afas, Marron, & Ceulemans, 2005; Pearce, Millard, Bray, & Rood, 2005; Dillen, Marron, Koch, & Ceulemans, 2008), which is in turn related to higher transpiration and lower WUE (Monclus et al., 2006; Pearce et al., 2005). In southern Italy (Navarro et al., 2014) P. deltoides genotypes “Dvina” and “Lena” were found as unsuitable SRC species in semi‐arid climatic conditions due to their low biomass production and their strong dependence on rainfall and soil water availability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed the highest stomatal ratio present in amphistomatous poplar species within Aigeiros section, where P. deltoides had 0.8-0.9, followed by Euroamerican poplars with 0.6-0.7 and the lowest values were presented by P. nigra 0.3-0.4 (Orlović 1992, Orlović et al 1999, Al Afas et al 2006, Dillen et al 2008, while few poplars from Tacamahaca section as hipostomatous species showed low ratio (Al Afas et al 2006Afas et al , 2007. Therefore, variations in stomatal characteristics among different poplar genotypes seem to be species specific (Al Afas et al 2006).…”
Section: Source Of Variationmentioning
confidence: 94%
“…et A.Gray ex Hook. and Populus balsamifera Lyall which belong to the section Tacamahaca which are the hypostomatous type, while Populus maximowiczii Henry, which belongs to the same section, is the amphistomatous type (Pearce et al 2006, Al Afas et al 2007, Dillen et al 2008. Populus nigra, as a part of section Aigeiros, is an amphistomatous species (Ceulemans et al 1995, Al Afas et al 2006, 2007, which was confirmed in our research, where the abaxial stomatal density (in average 161.46 per mm 2 ) was considerably higher than the adaxial stomatal density (in average 45.79 per mm 2 ) for all individuals and for all canopy positions (figure 3).…”
Section: Source Of Variationmentioning
confidence: 99%